Perancangan Aplikasi Pembelajaran Hukum Kepler Dengan Metode Integlligent Tuttoring System Berbasis Android - Nadya Putri Rizkia; Khairunnisa (Universitas Harapan Medan, 2021)
Along with the development of the times, the teaching methods carried out by teachers have changed, students are not only objects but also subjects, namely by reading, listening, and practicing, but it turns out that this condition can only be done in schools. Based on this research, a material that takes too long or a teaching model that is less practical, and does not attract students' attention. At times like this, a teaching model is needed, one of which is ITS learning using Adobe Flash. With this application, it is possible to know the shape and changes of the orbit by using interesting simulations so that students are more interested and understand Kepler's law more clearly.